1980
DOI: 10.1007/bf00281822
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal diastolic blood pressure and heart rate reactions to tilting in diabetes mellitus

Abstract: Summary. The orthostatic reaction to tilting was studied in 46 diabetics without symptoms of autonomic neuropathy and in 31 age-matched healthy control subjects. After tilting, the diastolic blood pressure rose in the control subjects but was unchanged or tended to fall in the diabetics, except in those of short duration without retinopathy. After tilting, the control subjects showed an immediate increase in heart rate with the highest value at 8.4 + 1.0 s (mean _+ SEM), followed by a transient decrease with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
3
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 17 publications
8
64
3
2
Order By: Relevance
“…Although we have concluded that cardiac autonomic alterations in diabetic neuropathy preferentially affects parasympathetic nerves, the parasympathetic neuropathic damage may not be distinct in other organs. Indeed, sympathetic neuropathies in the pupil 30 and peripheral nerves 31 were predominant in DM patients. Further study is needed to identify the effect of diabetic neuropathy not only on HRV but also on coronary artery tone for the purpose of early detection of neuroangiopathy, otherwise known as asymptomatic ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have concluded that cardiac autonomic alterations in diabetic neuropathy preferentially affects parasympathetic nerves, the parasympathetic neuropathic damage may not be distinct in other organs. Indeed, sympathetic neuropathies in the pupil 30 and peripheral nerves 31 were predominant in DM patients. Further study is needed to identify the effect of diabetic neuropathy not only on HRV but also on coronary artery tone for the purpose of early detection of neuroangiopathy, otherwise known as asymptomatic ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic nerve function was assessed from the heart rate reactions to deep breathing (expiration/inspiration ratio, a test of parasympathetic nerve function) [26] and to tilt (acceleration and brake indices, tests considering sympathetic nerve function as well) [27]. The blood pressure reaction to tilt was also assessed as a test of sympathetic nerve function.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…After 20 minutes at three different angles, the response was the same: a drop of BP and an increase in HR by more than 70% [25]. Another study guaranteed that 30 minutes of tilt and an angle of 60 degrees represent the best available resource to investigate the blood pressure fall [21,23].…”
Section: Discussionmentioning
confidence: 92%